Factors that influence the Level of Disclosure of Local Government Financial Statements: Faktor-faktor yang mempengaruhi Tingkat Pengungkapan Laporan Keuangan Pemerintah Daerah - Sappali, Winda Wahyuni; Kuntadi, Cris; Karunia, R Luki (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of relationships or influences between variables. This article reviews the factors that influence the level of disclosure of local government financial statements, namely local revenue, capital expenditure and audit findings, a study of human resource management literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The method of writing this scientific article is a qualitative method and library research which theories and relationships or influences between variables from books and journals both offline in the library and online. The results of this literature review article are: 1) Local Revenue affects the Disclosure Level of Local Government Financial Statements; 2) Capital Expenditure affects the Disclosure Level of Local Government Financial Statements; and 3) Audit Findings affect the Disclosure Level of Local Government Financial Statements. It is hoped that the results of this study can provide a deeper understanding of the factors that influence the disclosure of local government financial statements and find other factors that can affect the disclosure of local government financial statements.